(untitled) (Altre Modernità, 2011)
This paper analyses the way Paradise appears in different Theatre or Film productions of the XXth century: a biblical epos by the Israelian director Rina Yerushalmi, a film that became a classic, Children of Paradise (Carné, Prévert, 1943), the last show of the Living Theater, Paradise now (1968), and a film by Peter Weir, Truman Show (1998). In all of these productions, the Serpent, deeply negative in the biblical text appears like a positive figure, a kind of Messiah.